(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The article examines the current state of infrastructure asset management in Uzbekistan in the context of ongoing economic reforms, large-scale public investment programs, and the country’s strategic focus on sustainable and digitally driven development. The study analyzes the structural characteristics of infrastructure assets, including transport, energy, utilities, and social infrastructure, and evaluates existing management practices from the perspective of efficiency, lifecycle cost control, and long-term value creation. Particular attention is paid to the institutional environment shaping infrastructure asset management, including regulatory frameworks, governance mechanisms, ownership models, and the role of public–private partnerships. The research highlights key systemic challenges such as fragmented institutional responsibilities, limited integration of digital tools, insufficient performance-based management approaches, and constraints in investment planning and monitoring. At the same time, emerging opportunities associated with digital transformation, data-driven decision-making, and alignment with international asset management standards are identified. The article substantiates that improving institutional coordination, strengthening regulatory capacity, and adopting modern asset management methodologies are critical prerequisites for enhancing the resilience, efficiency, and sustainability of infrastructure development in Uzbekistan. The findings contribute to the academic discourse on infrastructure economics and provide practical insights for policymakers involved in public asset governance and long-term infrastructure planning.